Urban Poor Perceptions of Violence and Exclusion in Colombia - Moser, Caroline; McIlwaine, Cathy (Washington, DC: World Bank, 2013)
The study documents how people living in poor urban communities in Colombia, perceive violence, and identifies, the categories of violence affecting communities, the costs of different types of violence, the effect of violence on social capital, and the causes, and effects of social exclusion. Social institutions were identified across the nine research communities, making the distinction between those institutions benefiting the community, i.e., those creating positive social capital, and those institutions benefiting their members, while hurting the community, i.e., creating perverse social capital. The first group, which included primarily schools, and health centers, were mostly trusted, whereas those institutions dealing with the prevention of violence, such as state security, and justice institutions, were the least trusted. Interestingly, perverse organizations were the most prevalent membership organizations, including guerrilla type, and paramilitary groups, perpetrating political violence, and exercising a dominant force. The study identified avoidance, confrontation, conciliation, and other lesser strategies, as forms to deal with violence, and recommendations suggest the need to address the serious problem of displaced people, the unemployment situation, and above all, the need for peace negotiation, to abolish the pervasive nature of political violence.